A tutela indemnizatória do privado No âmbito da contratação pública: em especial, A “perda de chance” - António, Isa (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2018)
The compensation for the “loss of chance” is a third category of contractual interest, whereby the individual can be compensated by the contracting authority in the context of the pre-contractual procedure. The financial compensation of the positive contractual interest and negative contractual interest does not, in our view, cover the whole multi-faceted range of situations giving rise to damage to the legal-patrimonial sphere of the candidate. The “loss of chance” allows us to overcome the evidential difficulties associated with the theory of adequate causality, strict and of the “all or nothing” type, and it is also of central importance quantifying the indemnity value. Consequently, it consists of a mechanism for overcoming the difficulties in recognizing compensation for the private. The main issues raised in our study are the following: a) Under what circumstances are the public contracting authorities linked to the adjudication act or the conclusion of the contract? b) Can public contracting authorities “revoke their decision of contracting”? c) In case of affirmative answer, in which situations and what are the rights of private? d) What is the scope of the financial redress granted to the private illegally preempted in the pre-contractual procedure?